Prevalence of depression among patients with chronic pancreatitis: A systematic review and meta-analysis - Beas, Renato (2023)
Introduction: Chronic Pancreatitis (CP) is a fibroinflammatory condition with debilitating symptoms. Quality of life is severely affected in patients with CP and they are likely to suffer from mental health disorders, including depression. We conducted a systematic review and meta-analysis assessing the prevalence of depressive symptoms and depression in patients with CP. Methods: MEDLINE (OVID), PsycINFO, Cochrane Library, Embase, CINAHL Complete, Scopus and Web of Science were searched until July 2022 to identify manuscripts reporting the prevalence of depressive symptoms and depression (diagnosed clinically or with a validated scale without language restriction) in patients with Chronic Pancreatitis. The pooled prevalence was calculated using a random effects model. Heterogeneity was assessed by the inconsistency index (I2). Results: Among 3647 articles identified, 58 studies were identified for full text review, and ultimately nine studies were included. A total of 87,136 patients were included in the studies. Depression was diagnosed clinically or symptoms were identified using validated scales including Center for Epidemiological Studies 10-item Depression Scale (CESD), Beck Depression Inventory (BDI) and Hospital Anxiety and Depression Scale (HADS). The overall prevalence of depression in patients with chronic pancreatitis was 36.2% (95%CI: 18.8–55.7). In the stratified analysis, depression prevalence according to the clinical diagnosis, BDI and HADS was 30.10%, 48.17% and 36.61%, respectively. Conclusion: The high prevalence of depression among patients with CP deserves a call-to-action due to its medical implications and worsening quality of life. Our findings raise awareness of the importance of screening patients with CP for mental health disorders. Further well-designed studies are needed to further characterize these findings.